Functional consequences of TCF4 missense substitutions associated with Pitt-Hopkins syndrome, mild intellectual disability, and schizophrenia - Sirp, Alex; Roots, Kaisa; Nurm, Kaja; Tuvikene, Jürgen; Sepp, Mari; Timmusk, Tõnis (The journal of biological chemistry, 2021)
Transcription factor 4 (TCF4) is a basic helix-loop-helix transcription factor essential for neurocognitive development. The aberrations in TCF4 are associated with neurodevelopmental disorders including schizophrenia, intellectual disability, and Pitt-Hopkins syndrome, an autism-spectrum disorder characterized by developmental delay. Several disease-associated missense mutations in TCF4 have been shown to interfere with TCF4 function, but for many mutations, the impact remains undefined. Here, we tested the effects of 12 functionally uncharacterized disease-associated missense mutations and variations in TCF4 using transient expression in mammalian cells, confocal imaging, in vitro DNA-binding assays, and reporter assays. We show that Pitt-Hopkins syndrome-associated missense mutations within the basic helix-loop-helix domain of TCF4 and a Rett-like syndrome-associated mutation in a transcription activation domain result in altered DNA-binding and transcriptional activity of the protein. Some of the missense variations found in schizophrenia patients slightly increase TCF4 transcriptional activity, whereas no effects were detected for missense mutations linked to mild intellectual disability. We in addition find that the outcomes of several disease-related mutations are affected by cell type, TCF4 isoform, and dimerization partner, suggesting that the effects of TCF4 mutations are context-dependent. Together with previous work, this study provides a basis for the interpretation of the functional consequences of TCF4 missense variants.
Gesehen am 21.02.2022